The importance of evaluating metal exposure and predicting human health risks in urban–periurban environments influenced by emerging industry. (May 2016) - Yousaf, Balal; Amina; Liu, Guijian; Wang, Ruwei; Imtiaz, Muhammad; Rizwan, Muhammad Shahid; Zia-ur-Rehman, Muhammad; Qadir, Abdul; Si, Youbin
Abstract: The human population boom, urbanization and rapid industrialization have either directly or indirectly resulted in the serious environmental toxification of the soil-food web by metal exposure from anthropogenic sources in most of the developing industrialized world. The present study was conducted to analyze concentrations of Cd, Cr, Cu, Mn, Ni, Pb, and Zn in soil and vegetables in the urban–periurban areas influenced by emerging industry. Vegetables and their corresponding soil samples were collected and analyzed for heavy metals contents from six random sites. According to the results, the potential health risks from metals to the local communities were assessed by following the methodology described by the US-EPA. In general, the total non-carcinogenic risks were shown to be less than the limits set by the US-EPA. However, the potential risk of developing carcinogenicity in humans over a lifetime of exposure could be increased through the dietary intake of Cd, Cr and Ni. In some cases, Pb was also marginally higher than the safe level. It was concluded that some effective remedial approaches should be adopted to mitigate the risks of Cd, Cr, Ni and Pb in the study area because these metal levels have exceeded the safe limits for human health. However, new studies on gastrointestinal bioaccessibility in human are required to heighten our understanding about metals exposure and health risk assessment. Graphical abstract: Highlights: The metal exposures in the urban–periurban environments of an emerging industrial city were assessed. The health risks of metal contaminants via dietary exposure were estimated for local inhabitants. The predicted risks of developing cancer from lifetime exposures of Cd, Cr and Ni in adults exceeded the safe level.